2011
DOI: 10.3382/ps.2010-01215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental zinc source and level on growth performance, carcass traits, and meat quality of broilers

Abstract: The objective of this study was to investigate the effects of dietary supplemental Zn on growth performance, carcass traits, and meat quality of broilers. Dietary treatments included the corn-soybean meal-based diet (control) and the basal diet supplemented with 60, 120, or 180 mg of Zn/kg as ZnSO(4), Zn amino acid A, Zn proteinate B, or Zn proteinate A. The results showed that birds fed diets supplemented with Zn had higher ADFI, ADG, and percentage of eviscerated yield than birds fed the control diet. Supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
61
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 26 publications
12
61
0
5
Order By: Relevance
“…This is consistent with Liu et al (2011), who stated that dietary Zn levels and sources did not influence the abdominal fat percentage or the carcass traits of broilers. Rossi et al (2007) and Anil et al (2012b) reported that carcass yields were Savari et al (2015) concluded that there was no influence of ZnO on carcass traits.…”
Section: Carcass Yield Meat Quality and Blood Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with Liu et al (2011), who stated that dietary Zn levels and sources did not influence the abdominal fat percentage or the carcass traits of broilers. Rossi et al (2007) and Anil et al (2012b) reported that carcass yields were Savari et al (2015) concluded that there was no influence of ZnO on carcass traits.…”
Section: Carcass Yield Meat Quality and Blood Parameterssupporting
confidence: 92%
“…Jahnian & Rasouli (2015) reported no effects on plasma zinc concentration when inorganic zinc was replaced by Zn-methionine. Increased blood Zn levels are used as an indication of its biological availability in live animals (Liu et al, 2011). Similar findings were reported by Mohanna & Nys (1999) and , who observed that blood Zn concentration increased with dietary Zn content.…”
Section: Carcass Yield Meat Quality and Blood Parameterssupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, Zn enzymes are involved in the synthesis and/or breaking down of carbohydrates, lipids, proteins, and nucleic acids, and encompass all known classes of enzymes (Liu et al, 2011). The recommended Zn requirement that is based on performance criterion for broiler chickens is 40mg/kg of diet Nation Research Council (NRC, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that dietary Zn concentrations enhanced digestibility of fat by stimulating activities of the fat metabolism-related enzymes. Liu et al (2011) suggested that dietary Zn supplementation improved Zn status and resulted in promoting antioxidant ability and activities and gene expressions of fat metabolism-related enzymes of broilers. Similar results have been reported in mink (Bleavins et al 1983) and nursery pigs (Hill et al 2014).…”
Section: Discussionmentioning
confidence: 99%